Analisis Daya Dukung Pondasi Pada Perencanaan Gudang Menggunakan Metode Mayerhof - Sofiana, Erlia (Universitas Negeri Surabaya, 2023)
In a development, the foundation is an important structure because it functions as a support for the building. The foundation withstands loads from above, so that the lower structure if something happens (earthquake, etc.) cannot fail first. Therefore, the foundation must be planned properly in order to achieve stability and security, because the foundation holds the load from the superstructure that passes through the column. with the allowable stress value according to the soil bearing capacity. With different soil conditions, in this case different depths and with a shallow groundwater table affecting the planning of the foundation, therefore it is necessary to analyze the bearing capacity of the soil. The purpose of this paper is to find out the Qijin value of the bearing capacity of the soil and its reinforcement using the Mayerhof method. The value of soil bearing capacity using the Mayerhof method is 78,293 kN/m2